Friedel–Crafts acylation of benzene derivatives in tunable aryl alkyl ionic liquids (TAAILs) - Swantje Lerch; Stefan Fritsch; Thomas Strassner (Beilstein Journal of Organic Chemistry, 2023)
An iron(III) chloride hexahydrate-catalyzed Friedel–Crafts acylation of benzene derivatives in tunable aryl alkyl ionic liquids (TAAILs) has been developed. Through optimization of the metal salt, reaction conditions and ionic liquids, we were able to design a robust catalyst system that tolerates different electron-rich substrates under ambient atmosphere and allows for a multigram scale.